Експериментальні дослідження з метою верифікації результатів палеопалінологічного аналізу (на прикладі розрізу Ак-Кая, Крим) - Юрченко, Т. І. (Київський національний університет імені Тараса Шевченка, 2017)
Виконано порівняльний аналіз спорово-пилкових спектрів одновікових відкладів із двох розчисток, розташованих в межах однієї археологічної пам`ятки. На основі високого ступеня їх подібності здійснено верифікацію результатів палінологічного аналізу основного розрізу. Обґрунтовано правомірність застосування спорово пилкового аналізу при реконструкціях давньої рослинності та достовірність отриманих на його основі палеогеографічних висновків.

The comparative analysis of pollen spectra has been fulfilled for the two sections of the same age deposits at the Ak-Kaya archaeological site (Crimea). The pollen samples under study had been taken from the same genetic horizons of chernozem soils or their derivatives. Chronostratigraphy in both sections is based on the archaeological artifacts dating (time resolution 20-50 years). The cultural layers of the III-I cent. BC and VIII cent. AD are represented in the multilayered settlement. Almost identical pollen composition of the dominants of palynospectra has been revealed in the same age deposits of the two sections. The larger numbers of palynotypes have been determined in the main section of the site sampled with the higher resolution, but a pollen percentage of these palynotypes are very small and does not affect the transfer functions between the composition of fossil pollen spectra and the reconstructed palaeovegetation. For example, in the AP group few pollen grains of such plants as birch, willow, oak, linden, ash, maple, buckthorn, elder, viburnum, spindle-tree, Tatarian honeysuckle, ivy, heather family are present in small quantities only in 1-3 samples from 22 of them. In the NAP group, small quantities of pollen of Liliaceae, Alliaceae, Cannabaceae, Urticaceae, Linaceae, Geraniaceae, Rutaceae, Valerianaceae, Solanaceae, Euphorbiaceae, Campanulaceae, Boraginaceae, Lythraceae and Amaranthaceae families, several palynotypes of Plumbaginaceae, Leontice, Nuphar, Cirsium, Serratula, Rumex, Sedum occur only in 1-4 samples. Spores of Equisetum, Ophioglosum, Pteridium and Sphagnum were found only in 1-2 samples of one of the sections. The main indices: a ratio between AP, NAP and spores, pollen percentages of dominants in the AP (pine, alder, hornbeam, hazel) and the NAP (Herbetum mixtum, Poaceae, Cyperaceae, Asteraceae and Cichoriaceae) are practically identical, as well as pollen percentages of synanthropic plants (particularly Cerealia). The changes in dominants of pollen zones under comparison are the same in both sections, and they reflect the same changes in vegetation of the area: from shrub steppe with diversity of mesophytic herbs (the beginning of III cent. BC) to the steppe with predominance of grasses over herbs (the middle part of the III cent. BC) and to the forb-grass steppe (the end of the III cent. BC). The climate of these time span changed from the similar to the modern one up to rather dry. The VIII cent. AD was characterized by rather mesophytic vegetation in both sections and, so, by more humid climate then nowadays. Thus, the study fulfilled demonstrates a reliability of results of pollen analysis in order to reconstruct palaeovegetation and to trace a palaeoclimatic change.
Experimental studies for verification of the results of the palaeopalynological analysis (a study case of the Ak-Kaya archaeological site, Crimea)
Keywords: спорово-пилковий спектр; палінозона; палінодіаграма. палеорослинність; pollen spectrum? palynozones; palynodiagrams